Effectiveness of Noise-Attenuating Headphones on Physiological Responses for Children With Autism Spectrum Disorders - Pfeiffer, Beth; Stein Duker, Leah; Murphy, AnnMarie; Shui, Chengshi (Frontiers in Integrative Neuroscience, 2019)
OBJECTIVE: The purpose of this study was to evaluate the proof of concept of an intervention to decrease sympathetic activation as measured by skin conductivity (electrodermal activity [EDA]) in children with an Autism Spectrum Disorder (ASD) and auditory hypersensitivity (hyperacusis). In addition, researchers examined if the intervention provided protection against the negative effects of decibel level of environmental noises on electrodermal measures between interventions. The feasibility of implementation and outcome measures within natural environments were evaluated. METHOD: A single subject multi-treatment design was used with six children, aged 8-16 years with a form of Autism (i.e., Autism, PDD-NOS). Participants used in-ear and over-ear headphones for two randomly sequenced treatment phases. Each child completed four phases: 1) a week of baseline data collection, 2) a week of an intervention, 3) a week of no intervention, and 4) a week of the other intervention. Empatica E4 wristbands collected electrodermal activity data. Data was collected on 16-20 occasions per participant, with five measurements per phase. RESULTS: Separated tests for paired study phases suggested that regardless of intervention type, noise attenuating headphones led to a significant difference in frequency of both skin conductance levels (SCL) and non-specific skin conductance responses (NS-SCR) between the baseline measurement and subsequent phases. Overall, SCL and NS-SCR frequency significantly decreased between baseline and the first intervention phase. A protective effect of the intervention was tested by collapsing intervention results into three phases. Slope correlation suggested constant SCL and NS-SCR frequency after initial use of the headphones regardless of the increase in environmental noises. A subsequent analysis of the quality of EDA data identified that later phases of data collection were associated with better data quality. CONCLUSION: Many children with ASD have hypersensitivities to sound resulting in high levels of sympathetic nervous system reactivity, which is associated with problematic behaviors and distress. The findings of this study suggest that the use of noise attenuating headphones for individuals with ASD and hyperacusis may reduce sympathetic activation. Additionally, results suggest that the use of wearable sensors to collect physiological data in natural environments is feasible with established protocols and training procedures.